Bioatividade de extratos a usos de Eucalyptus sp. L'Hér. (Myrtaceae) e Melia azedarach L. (Meliaceae) sobre Musca domestica L. (Diptera, Muscidae) - Freitas, Sabrina Rodrigues Quadro de (2008)
The extracts of vegetal origin have been largely studied with the aim of obtaining an efficient and ecologically viable alternative to the control of plagues.The study of substances with selective deterrent bioactivity that affects insect s behavior, development and reproductive output is extremely important to avoid the problems caused by non selective chemical insecticides.Based in the importance of Musca domestica L.(Diptera,Muscidae)due to its high potential of carrying pathogens,its occurrence in high populations and in the lack of studies about the effects of vegetal extracts over insects,the present study was carried out with the objective of evaluating the deterrent bioactivity of aqueous extracts of Eucalyptus sp. L'Hér. (Myrtaceae)and Melia azedarach L.(Meliaceae)over larvae of M. domestica and the influence of the aqueous extract of M. azedarach on the oviposition behavior of this insect.To evaluate the influence of the aqueous extracts of Eucalyptus sp.and M. azedarach on larvae of M. domestica...